Resilience and engagement in university students during the context of COVID 19 (Revista Innova Educación, 2020)
Resilience and engagement are mental capacities that allow a high possibility of overcoming stressful positions. The main purpose of the research was to determine the association between the levels of resilience and engagement (vigor, dedication and absorption) in the Accounting Sciences students of Universidad Nacional del Altiplano de Puno during the context of COVID 19, 2020. The method used It was the hypothetical deductive, descriptive type and cross-correlational design. The study was developed in the aforementioned Professional School and they voluntarily responded to the online questionnaires. The population consisted of 70 students from the third to the fifth semester (cycle 2020 I). The results indicate a significant association of 0.693 between resilience and engagement in Spearman's rho correlation coefficient. In conclusion, resilience is positively associated with engagement in Accounting Sciences students at the Universidad Nacional del Altiplano de Puno.
Keywords: Engagement; students; resilience; university